2009
DOI: 10.1080/08897070903041228
|View full text |Cite
|
Sign up to set email alerts
|

Legal Ages for Purchase and Consumption of Alcohol and Heavy Drinking among College Students in Canada, Europe, and the United States

Abstract: Heavy drinking and associated negative consequences remain a serious problem among college students. In a secondary analysis of data from two published study, the authors examine the correlation between minimum legal age to purchase and/or consume alcohol and rates of heavy drinking among college students in 22 countries. The published studies use identical definitions of heavy drinking and similar methodologies. In the study of 20 European countries and the United States, there is a positive correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…It is notable that the reduced proportion of young people who drank alcohol in the period 2002–2010 followed the introduction of age limits for purchasing alcohol. The observation of less frequent alcohol drinking among adolescents after introduction of age limit restrictions corresponds with similar findings in studies from the United States (Keller, Frye, Bauerle, & Turner, ; Norberg, Bierut, & Grucza, ) and Denmark (Rheinländer & Nielsen, ). The gender differences in trends changed from being nonsignificant to significant in the two time spans studied.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is notable that the reduced proportion of young people who drank alcohol in the period 2002–2010 followed the introduction of age limits for purchasing alcohol. The observation of less frequent alcohol drinking among adolescents after introduction of age limit restrictions corresponds with similar findings in studies from the United States (Keller, Frye, Bauerle, & Turner, ; Norberg, Bierut, & Grucza, ) and Denmark (Rheinländer & Nielsen, ). The gender differences in trends changed from being nonsignificant to significant in the two time spans studied.…”
Section: Discussionsupporting
confidence: 87%
“…However, strong evidence for a direct causal relationship between age limits and alcohol use cannot be claimed based on our ecological observations and analyses. Although many young people succeed in buying alcohol despite age limits (Dent, Grube, & Biglan, ; Forster, Murray, Wolfson, & Wagenaar, ; Paschall et al., ; Preusser & Williams, ; Rossow, Karlsson, & Raitasalo, ; Rossow, Storvoll, & Pape, ), the general observation is that age limits reduce the proportion of young people who buy and drink alcohol frequently (Casswell & Zhang, ; Jørgensen et al., ; Keller et al., ; Norberg et al., ). The general observation also indicates a reduction in the proportion of those who suffer from alcohol‐induced problems such as injuries and drunken driving (Fell, Fisher, Voas, Blackman, & Tippetts, , ; Kypri et al., ; Yu & Shacket, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study, as well as studies in many other countries, showed that more men are drinking alcohol and more men are binge drinkers than women ( 3 , 5 , 6 , 20 , 22 , 24 , 27 , 29 , 31 ). This result is not surprising as drinking alcohol historically was more or less men’s domain, but in the last decades things are changing.…”
Section: Discussionsupporting
confidence: 79%
“…While there were many studies done among university students in Europe ( 20 22 ), only a few local research projects have been conducted in Slovenia, but they have not used standardized questions about alcohol drinking ( 23 – 26 ), except for one that was conducted among the students of the University of Ljubljana ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Almost all European and North American countries have minimum purchasing ages (MPA) for alcohol, typically from 16 to 21 years . Although many young people succeed in buying alcohol despite age limits , the general observation is that low MPA is associated with a higher proportion of young people who buy and drink alcohol and the proportion who experience problems from their alcohol use such as injuries and drunk driving . Restrictions on advertising and availability have also been used to reduce alcohol consumption and related harm among adolescents .…”
Section: Introductionmentioning
confidence: 99%